Efficacy of the melanocortin analogue Nle4‐D‐Phe7‐α‐melanocyte‐stimulating hormone in the treatment of patients with Hailey–Hailey disease. (1st March 2014) - Biolcati, G.; Aurizi, C.; Barbieri, L.; Cialfi, S.; Screpanti, I.; Talora, C.
Summary: Background: Hailey–Hailey disease (HHD) is a rare, chronic and recurrent blistering disorder, which is characterized clinically by erosions occurring primarily in intertriginous regions, and histologically by suprabasal acantholysis. Oxidative stress plays a specific role in the pathogenesis of HHD, by regulating the expression of factors playing an important role in keratinocyte proliferation and differentiation. Aim: Given the significance of oxidative stress in HHD, we investigated the potential effects of the antioxidant properties of an α‐MSH analogue, Nle4‐D‐Phe7‐α‐MSH (afamelanotide), in HHD lesion‐derived keratinocytes. Results: Treatment of HHD‐derived keratinocytes with afamelanotide contributed to upregulation of Nrf2 [nuclear factor (erythroid‐derived 2)‐like 2], a redox‐sensitive transcription factor that plays a pivotal role in redox homeostasis during oxidative stress. Additionally, afamelanotide treatment restored the defective proliferative capability of lesion‐derived keratinocytes. Our results show that Nrf2 is an important target of the afamelanotide signalling that reduces oxidative stress. Because afamelanotide possesses antioxidant effects, we also assessed the clinical potential of this α‐MSH analogue in the treatment of patients with HHD. In a phase II open‐label pilot study, afamelanotide 16 mg was administered subcutaneously as a sustained‐release resorbable implant formulation to two patients with HHD, who had a number of long‐standing skin lesions. For both patients, their scores on the Short Form‐36 improved 30 days after the first injection of afamelanotide, and both had 100% clearance of HHD lesions 60 days after the first injection, independently of the lesion location. Conclusions: Afamelanotide is effective for the treatment of skin lesions in HHD.